Differences in trabecular bone texture between knees with and without radiographic osteoarthritis detected by directional fractal signature method - Wolski, M.; Podsiadlo, P.; Stachowiak, G. W.; Lohmander, Stefan ; 0000-0002-5424-9448; Englund, Martin ; 0000-0003-3320-2437 (Osteoarthritis and Cartilage, 2010)
Objective: To evaluate differences in tibial trabecular bone (TB) texture between subjects with and without radiographic knee osteoarthritis (OA) using a variance orientation transform (VOT) method. Design: Subjects with knee OA (Kellgren & Lawrence grade >= 2) and controls without OA (both n = 26, seven women) were matched by sex, age, body mass index and compartment. The VOT method was applied to TB X-ray images and fractal signature and dimension in horizontal (FSH, FDH) and vertical (FSV, FDV) directions and along the roughest part of TB (FSSta, FDSta), texture aspect ratio (Str) and signature (StrS), and mean FD (FDMEAN) were calculated. The VOT method was compared against an augmented Hurst orientation transform (HOT) method using paired t tests, intraclass correlation coefficients (ICCs) and coefficients of variation (CVs%). Longitudinal sensitivity to OA bone changes was not assessed. Results: For the reproducibility of texture parameters, ICCs were >0.75 and CVs% were <8.2% for both methods. Compared with controls, FDMEAN, FDH, FDV and FDSta for OA knees were lower (P < 0.001), while Str was higher in both medial (P = 0.03) and lateral (P = 0.02) compartments. FSH, FSSta were lower for OA knees than for controls at sizes 0.3-0.7 mm (P < 0.001) in both compartments. In lateral compartment, FSV for OA knees was lower than for controls at sizes 0.3-0.5 mm (P < 0.001) and 0.55-0.70 mm (P < 0.02), while in medial compartment at sizes 0.3-0.7 mm (P < 0.001). Compared with controls, StrS for OA knees was higher at sizes 0.3, 0.55-0.70 mm in medial (P < 0.03) and lateral (P < 0.04) compartments. Conclusions: The VOT method is comparable to HOT method in the reproducibility of texture parameters and the ability to discriminate between non-OA and OA TB textures. However, unlike the HOT method, it quantifies texture roughness along the roughest part of the tibial bone, texture anisotropy at individual trabecular sizes and it works over a larger range of trabecular sizes. The VOT method may be a valuable tool for studying OA changes in TB. (C) 2010 Osteoarthritis Research Society International. Published by Elsevier Ltd. All rights reserved.
Keywords: Osteoarthritis; Fractal analysis; Plain radiography; Trabecular bone